2007
DOI: 10.1179/146532807x245670
|View full text |Cite
|
Sign up to set email alerts
|

Genital lesions complicating female genital cutting in infancy: a hospital-based study in south-east Nigeria

Abstract: Childhood FGC contributes to appreciable morbidity among girls, a large proportion of whom are not managed in a hospital setting. The cost of managing these complications can be enormous, especially in low-resource settings. Girl child education to tertiary level and the involvement of traditional rulers and local decision-makers in the campaign against FGC might help to eradicate the practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…This may be a direct reflection of the current prevalence and poor surgical techniques of female genital mutilation in this African subregion. As also reported in earlier studies, 10,11 cases that died following the mutilation and those who could cope with the complications may not have been discovered and/or reported to appropriate quarters. This scenario has adversely affected proper documentations on female genital mutilation in many cultures.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…This may be a direct reflection of the current prevalence and poor surgical techniques of female genital mutilation in this African subregion. As also reported in earlier studies, 10,11 cases that died following the mutilation and those who could cope with the complications may not have been discovered and/or reported to appropriate quarters. This scenario has adversely affected proper documentations on female genital mutilation in many cultures.…”
Section: Discussionmentioning
confidence: 69%
“…Labial adhesion and other vulval complications have been reported following the different types, but clitoral epidermoid inclusion cyst is reported 10,11,18 to be exclusively associated with clitoral tip excision (type I). This corresponds with findings in this study in which all the clitoral cysts were found to occur following clitoral tip excision as the cyst arose and attached to the remaining stump.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations